Can the Curriculum of Creativity Affect Motivation to Dance? - Ušpurienė, Aistė Barbora (Pedagogika, 2023)
The aim of this study is to investigate whether the curriculum of creativity affects motivation to dance. The experiment was conducted. Forty dancers were divided into experimental and control groups. The experiment was carried out for sixteen weeks. Dancers in the control group were educated according to a regular programme designed by the teacher, while dancers in the experimental group were given the creativity curriculum. To assess the effect of different curricula on dancers’ motivation, a questionnaire survey was conducted at the beginning and at the end of the experiment.